Corporate governance of state-owned enterprises change and reform in OECD countries since 2005 - OECD (Paris OECD, 2011)
In 2005, OECD published a stocktaking of the corporate governance framework in the Organisations member countries. This publication was the basis on which the OECD Guidelines on Corporate Governance of State-Owned Enterprises (the SOE Guidelines) was developed. It has been widely quoted in academic literature, in official documents and by practitioners. However, the SOE landscape in OECD countries has changed significantly since 2005 and four new countries have become members of the Organisation. This publication provides an update of changes since 2005, organised according to the main sections of the SOE Guidelines: the legal and regulatory framework for SOEs; the state acting as an owner; equitable treatment of shareholders; relations with stakeholders; transparency and disclosure, and the responsibilities of the boards of SOEs.
This document updates the earlier publication OECD (2005), Corporate governance of state-owned enterprises: a survey of OECD countries
Keywords: Corporate Governance, Business Enterprisess OECD Countries